⬇ Hey, the answer is down below! :) ⬇
For y: x = -3
For y it stays the same.
For x: y = 2
For x it stays the same too.
For 1.): [tex]x = \frac{1}{6}y + \frac{-4}{3}[/tex]
Step-by-step explanation:
For y there is no step-by-step explanation unfortunately.
For x there isn't a step-by-step explanation too unfortunately.
⬇ For 1.) there is a step-by-step explanation! ⬇
For step 1 we should flip the equations.
6x + 8 = y
For step 2 we should add -8 to both sides.
6x + 8 + − 8 = y + −8
= 6x = y − 8
For step 3 we should divide both sides by 6.
[tex]\frac{6x}{6} = \frac{y - 8}{6}[/tex]
= x = [tex]x = \frac{1}{6}y + \frac{-4}{3}[/tex]
In result we should have [tex]x = \frac{1}{6}y + \frac{-4}{3}[/tex] as the answer!